(untitled) (Eurasian Journal of Philology Science and Education, 2019)
The article examines the work of Oralkhan Bokei, who is one of the first to touch upon the problem of artistic essay in Kazakh journalism, journalistic motives in his works also the skill to rely on life principles in describing his contemporaries, bright signs of modernism in his creative direction, features of the use of language means, the author’s customary and convenient methods of decoration were also analyzed. The textual comparisons are made about the problem of creative laboratories for the development of the literary heritage of the writer Oralkhan Bokey in the context of the influence of fiction on his journalistic experience, the fact is that most of the works are artistic stories, short stories, storytelling of the novel through creative development from an artistic essay for the first time special attention was given to the study. Although this issue is rarely discussed in our work, comparing the works “The Character of Sand”, “Where are You, My White-Foal Foal” and “Country and Land”, we drew attention to the fact that Oralkhan Bokey was a significant factor in writing. The striking sensory intuition of the writer, which creates works at the level of new views in world literature, quick-witted consciousness, thought, the best examples of ideas, to take writing seriously as cumulative and analytical models, an attempt was made to understand mysterious images.